دور الحرارة و الأغلفة في إنبات الخوخ الشائك L) Prunus spinosa) وخوخ الدب (L Prunus ursina) - دواي فيصل; اسماعيل هيثم; صبوح صفاء (Latakia University Journal -Biological Sciences Series, 2019)
أجريت التجارب على إنبات نوى و بذور وأجنة نوعي الخوخ الشائك L P.spinosa و خوخ الدب L P.ursina في مركز البحوث العلمية الزراعية باللاذقية، جمعت الثمار الناضجة من المواقع (كسب,جبلة,الحفة ). تمت زراعة نوى و بذور وأجنة النوعين المدروسين على وسط آجار0.7% في الظلام في درجات الحرارة (5-10-15-20مْ). بينت النتائج عدم إنبات نوى النوعين المدروسين في جميع درجات الحرارة المستخدمة، بينما أدى كسر الغلاف الخشبي إلى إنبات البذور، حيث كانت أفضل نسبة إنبات لبذور الخوخ الشائك 100% ،ولبذور خوخ الدب 92% وذلك في الدرجة 5مْ. وكانت نسب إنبات أجنة النوعين المدروسين مرتفعة في جميع درجات الحرارة المستخدمة. The experiment was carried out in Lattakia research center to study the role of temperature and seed coat in seed germination of P. spinosa L and P.ursina L. Ripe fruits were collected from (Kasab, Jabla and Alhaffa). The Seeds were sown at Agar-medium 0.7% in the dark at different control germination temperatures (5Cº-10C°-15 C° and 20C°). Results showed that the seeds with coats of both species did not germinate in all temperatures, while removing the crust of the woody coat of P. spinosa L and P .ursina L seeds made them germinate. The best germination of seeds without coat was 100% for P. spinosa L and 92% for P. ursina L at 5 C°. The germination of the embryos of both species was high at all temperatures.